2010
DOI: 10.1016/j.rmed.2010.03.008
|View full text |Cite
|
Sign up to set email alerts
|

The use of non-routine pleural fluid analysis in the diagnosis of pleural effusion

Abstract: The investigation of a pleural effusion is, in general, a very straight forward process with the combination of clinical history, examination, radiology and pleural fluid analysis leading to diagnosis in most cases. While most fluid samples are sent for routine analysis including protein, LDH, glucose, cytology and microbiology, there are a number of more unusual fluid analyses available which in some cases directly lead to, and in others are suggestive of the diagnosis. Moreover, other fluid markers are const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Consequently, the development of noninvasive methods is important to differentially diagnose these two diseases, including clinical decision trees 12 and nonroutine pleural fluid analysis (eg, ADA). 13 Accordingly, various PE biomarkers released during the immune response triggered by the presence of mycobacterial antigens or tumors in the pleural space have been investigated, such as ADA and interferon-g (IFN-g), particularly as well-recognized biomarkers for TPE, 14 , 15 but the diagnostic methods and performance seem to be variable. Thus, the objective of our study was to investigate PE biomarkers according to TB and cancer immunology to help distinguish these two common lymphocyte-predominant exudative PEs.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the development of noninvasive methods is important to differentially diagnose these two diseases, including clinical decision trees 12 and nonroutine pleural fluid analysis (eg, ADA). 13 Accordingly, various PE biomarkers released during the immune response triggered by the presence of mycobacterial antigens or tumors in the pleural space have been investigated, such as ADA and interferon-g (IFN-g), particularly as well-recognized biomarkers for TPE, 14 , 15 but the diagnostic methods and performance seem to be variable. Thus, the objective of our study was to investigate PE biomarkers according to TB and cancer immunology to help distinguish these two common lymphocyte-predominant exudative PEs.…”
Section: Introductionmentioning
confidence: 99%
“…Interferon-γ, a cytokine released from CD4 + lymphocytes, is elevated in TBPE [11], [15]. A recent meta-analysis revealed that this has a sensitivity of 89% and a specificity of 97% when diagnosing TB [16].…”
Section: Discussionmentioning
confidence: 99%
“…9 ADA is an enzyme that converts adenosine to inosine-deoxyadenosine to deoxyinosine in purine catabolism that is dominantly found on T cells, that plays an important role in cell differentiation, and that shows immune cell activity. 10 ADA has two isoenzymes: ADA1 and ADA2. While ADA1 isoenzyme is found in many cells, ADA2 enzyme is only produced by monocytes/macrophages and constitutes the main component of increased ADA activity in TPE.…”
Section: Adenosine Deaminasementioning
confidence: 99%